Comparative Profiling of Four Lignans (Phyllanthin, Hypophyllanthin, Nirtetralin, and Niranthin) in Nine Phyllanthus Species from India Using a Validated Reversed Phase HPLC-PDA Detection Method. (30th September 2020) - Patel, Jinal; Nagar, Padamnabhi Shanker; Pal, Kalpana; Singh, Raghuraj; Dhanani, Tushar; Patel, Vyomesh; Srivastava, Sharad; Kumar, Satyanshu
Abstract: Background: Phyllanthus species exhibit a wide range of in vitro and in vivo pharmacological activities; however, little is known about the compounds present in the extracts that are responsible for such actions. Objective: Development and validation of a simple reversed phase HPLC-PDA method for profiling of phyllanthin, hypophyllanthin, nirtetralin, and niranthin in extracts of Phyllanthus species was carried out. Methods: Separation was achieved using an XBridge column ® (150 × 4.6 mm, 5.0 µm id) in an isocratic elution mode with mobile phase comprising of a mixture of acetonitrile and water with TFA (0.05%, v/v, pH = 2.15) at ambient temperature with a flow rate of 1 mL/min. Results: Phyllanthin, hypophyllanthin, nirtetralin, and niranthin were eluted at mean retention times of 10.47, 11.10, 13.67, and 14.53 min, respectively. LOD and LOQ for all four analytes were 0.75 and 3.00 μg/mL, respectively. RSDr values for intraday and interday precision for phyllanthin, hypophyllanthin, nirtetralin, and niranthin were 0.38–1.32 and 0.45–1.77%; 0.22–3.69 and 0.24–3.04%, 0.73–2.37 and 0.09–0.31%, and 1.56–2.77 and 0.12–0.68%, respectively. Conclusions: The developed and validated HPLC-PDA method was applied for identification and quantification of phyllanthin, hypophyllanthin, nirtetralin, and niranthin in extracts of different plant parts of selected Phyllanthus species. The outcome of the present investigation could be useful for selection of best species to promote its commercial cultivation and suitable extraction solvent for preparation of lignan-enriched fractions. This HPLC-PDA method could be useful for quality control of herbal formulations containing plants from Phyllanthus species.